The Conception of Kafa'ah in Building a Harmonious Family for Hafidz Al-Qur'an Maslahah Perspective (Case Study on Alumni of the Majelis Qurra' Wal Huffadz As'adiyah Jami' Mosque Sengkang) - Miftahuddin, Miftahuddin; Bakri, Muammar; Santalia, Indo (Pascasarjana UIN Alauddin Makassar, 2023)
This study aims to describe kafa'ah in building a harmonious family from a maslahah perspective by involving married alumni of the tahfidz al-Qur'an Majelis Qurra' Wal Huffadz As'adiyah Jami' Sengkang Mosque as research subjects through the stages of assessment; kafa'ah criteria, efforts to build a harmonious family and the conception of kafa'ah maslahah perspective in building a harmonious family. The research results show that the criteria for kafa'ah in building a harmonious family are dominated by; standard criteria on beauty and lineage, criteria on wealth, and social status. Both two criteria above will not be perfect without a review of the religious aspect, second, building a harmonious family from a maslahah perspective for hafidz al-Qur'an through the role of communication, appreciation, commitment, and spiritual aspects, financial stability, kafa'ah in religion and lineage, having the same goal, third, the conception of kafa'ah is shown; The Hufadz consistently say that the central concept of kafa'ah is seen from the religious and lineage aspects, marrying a partner who is equal in educational and social background, the context does not impose conditions such as the requirement to memorize the Qur'an thirty chapters.